2015
DOI: 10.1007/s00395-015-0506-5
|View full text |Cite
|
Sign up to set email alerts
|

NOS1 induces NADPH oxidases and impairs contraction kinetics in aged murine ventricular myocytes

Abstract: Nitric oxide (NO) modulates calcium transients and contraction of cardiomyocytes. However, it is largely unknown whether NO contributes also to alterations in the contractile function of cardiomyocytes during aging. Therefore, we analyzed the putative role of nitric oxide synthases and NO for the age-related alterations of cardiomyocyte contraction. We used C57BL/6 mice, nitric oxide synthase 1 (NOS1)-deficient mice (NOS1(-/-)) and mice with cardiomyocyte-specific NOS1-overexpression to analyze contractions, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…This increased activity in NOX activity in the aged heart has been proposed to depend on nitric oxide 1 (NOS1) [31] and on the renin-angiotensin system [8]. …”
Section: Discussionmentioning
confidence: 99%
“…This increased activity in NOX activity in the aged heart has been proposed to depend on nitric oxide 1 (NOS1) [31] and on the renin-angiotensin system [8]. …”
Section: Discussionmentioning
confidence: 99%
“…Of them, 37 miRNA–mRNA pairs showed significant negative expression correlations ( r < −0.5) through all three skeletal muscle development stages ( Table 5 ). Many mRNA genes have been reported as regulators of either muscle differentiation or development, including MyoD1 (Blum et al, 2012), CSRP2 (Herrmann et al, 2006), MBNL1 (Chen et al, 2016), FHOD1 (Staus et al, 2011), MET (Park et al, 2015), SOD1 (Sakellariou et al, 2018), RCAN1 (Emrani et al, 2015), SGCA (Fougerousse et al, 1998), SRF (Ding et al, 2017), MEF2A (Yuan et al, 2014), MTM1 (Bachmann et al, 2017), LBX1 (Chao et al, 2011), MEF2D (Runfola et al, 2015), IGFBP5 (Zhang et al, 2017), PDGFA (Tallquist et al, 2000), AMOT (Wang et al, 2018a), PDPK1 (Mora et al, 2003), SIRT2 (Arora and Dey, 2014), SIX4 (Chakroun et al, 2015), NOS1 (Villmow et al, 2015), MYL1 (Burguiere et al, 2011), ACTA1 (Hu et al, 2015), PROX1 (Kivela et al, 2016), and QKI (Wu et al, 2017). These interaction pairs included 7 known and 27 novel miRNAs, of which the miRNAs ssc-miR-744 (Yang et al, 2015), ssc-miR-497 (Sato et al, 2014), ssc-miR-338 (Mcdaneld et al, 2009), ssc-miR-423-3p (Siengdee et al, 2015), and ssc-miR-133a-3p (Wang et al, 2018c) were reported to have important roles in myogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, NOS1 was expressed in a subpopulation of atrial cardiomyocytes including myoendocrine cells and affected contraction of isolated myocytes. Moreover, in sarcoglycanopathies nNOS is a modulating factor in the course of muscular dystrophy ( Miethke et al, 2003 ; Angelini et al, 2014 ; Villmow et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%